2008
DOI: 10.1002/ibd.20322
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-refractory ulcerative colitis: Predictive factors of response to cyclosporine and validation in an independent cohort

Abstract: The Ho-based predictive score is a good predictor of response to cyclosporine and avoidance of colectomy, and may aid in the indication of this treatment for management of steroid-resistant UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
(26 reference statements)
0
37
0
3
Order By: Relevance
“…Although a few studies determined predictive factors of response to ciclosporin, there is no preferred index of response to intravenous ciclosporin in patients with severe UC. [17][18][19][20] Early prediction of the therapeutic response of ciclosporin is crucial because ciclosporin has been considered one of the final treatments for steroid-refractory severe UC patients before colectomy is considered. Recently, alternative drugs such as infliximab and adalimumab have emerged for the treatment of severe UC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies determined predictive factors of response to ciclosporin, there is no preferred index of response to intravenous ciclosporin in patients with severe UC. [17][18][19][20] Early prediction of the therapeutic response of ciclosporin is crucial because ciclosporin has been considered one of the final treatments for steroid-refractory severe UC patients before colectomy is considered. Recently, alternative drugs such as infliximab and adalimumab have emerged for the treatment of severe UC.…”
Section: Resultsmentioning
confidence: 99%
“…18 Aceituno et al reported that higher Ho index before initiation of ciclosporin is a predictor of colectomy, suggesting that lower serum albumin, wider transverse colon diameter on plain X-ray, and higher stool frequency predict colectomy. 19 In contrast, Rios et al identified three factors (older age, thrombocytosis, and a history of previous treatment with ciclosporin) as predictive factors for colectomy. 20 Multivariate analysis in our study first indicated that older age is an important factor predicting colectomy, similar to the report of Rios et al 20 Ulcer healing in the colonic mucosa is delayed in elderly patients compared to younger patients.…”
Section: * Statistically Significantmentioning
confidence: 95%
“…For patients admitted with severe UC, initial treatment with intravenous corticosteroids is recommended, with methylprednisone 40-60 mg/day as a bolus infusion. Corticosteroids should not be used as maintenance treatment because of the high probability of developing adverse events and corticosteroid-dependent disease [40,41]. Remission rates are significantly higher in UC patients receiving oral corticosteroids compared with placebo [42].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The former two parameters have been identified as predictive factors by previous studies. 6,8,9 The authors use these factors to propose a novel calculation formula and a decision tree analysis, which predicts colectomy with an accuracy of 90.4%, positive predictive value of 72.2% and negative predictive value of 100%. Most patients included in the study had disease refractory to other agents including one patient previously treated with tacrolimus and two patients having received infliximab induction therapy.…”
Section: -10mentioning
confidence: 99%